Mortality in residents of the urban and rural areas of Mexico, 2002-2019 - Debanhi Martínez-Téllez; Evelyn Martínez-Calderón; Patricia Esquivel-Ferriño; Lucia Cantú-Cardenas; Omar González-Santiago (James Cook University, 2023)
Introduction: Mortality is affected by several factors, including the place of residence. Several studies have found a gap in mortality between urban and rural residents. This study aimed to describe adjusted mortality rates in urban and rural areas of Mexico. Methods: Adjusted mortality rate per 100 000 inhabitants was estimated in urban and rural areas of Mexico, were grouped by sex, age, and main cause of death. Trend analysis was performed with a logarithmic regression of adjusted rates. Results: Mortality was higher in urban (622.1/100 000 inhabitants) than rural (549.5/100 000 inhabitants) areas of Mexico. Males showed the highest mortality rate in both studied areas, urban and rural (737.8 and 634.4/100 000 inhabitants respectively). A significant annual decrease of 0.5% in mortality rates was observed in both areas. Conclusion: In Mexico, there is a gap in mortality rates based on individuals' place of residence. Those who live in urban areas present the highest mortality rates.